Mechanically driven structural transformation in Sn reinforced Al–Cu–Fe quasicrystalline matrix nanocomposite - Shadangi Y.; Shivam V.; Varalakshmi S.; Basu J.; Chattopadhyay K.; Majumdar B.; Mukhopadhyay N.K. (My University, 2025)
In the present investigation efforts were made to study mechanically driven structural transformation in Sn reinforced Al–Cu–Fe icosahedral quasicrystalline (IQC) matrix nanocomposites. The sequence of structural transformation, phase composition, thermal stability and hardness of mechanically milled IQC-Sn nanocomposite powder were studied through X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), differential scanning caloriemtery (DSC) and nanoindentation techniques. The XRD result suggests the formation of nano-structured composites. The IQC phase co-existed with monoclinic Al13Fe4 (a = 1.549 nm, b = 0.808 nm, c = 1.248 nm, α = β = 90°, γ = 107.72°; mC102) and B2-type Al (Cu, Fe) (a = 0.29 nm; cP2) phase in IQC-Sn nanocomposite powder subjected to mechanical milling for 40 h. The structural transformation and fraction of IQC, Al13Fe4 and B2–Al (Cu, Fe) phase depends upon the volume fraction of Sn and duration of milling. The crystalline phases formed during milling transformed to a stable IQC phase along with the other crystalline phases during subsequent annealing treatment. The structural transformations occurring during milling have a remarkable effect on indentation hardness, which is in the range of ∼ 4–7 GPa. This suggests that IQC-Sn nanocomposite produced through milling with desirable mechanical properties may be used as potential coating materials for engineering applications. © 2020 Elsevier B.V.